Stochastyczne modelowanie zmian cen aktywów w podejmowaniu decyzji inwestycyjnych - Nita, Bartłomiej (Stochastic Modelling of Commodity Price Changes in Undertaking Investment Decisions, 2006)
The paper describes the importance of stochastic modelling of commodity process in undertaking investment decisions. In the first part of the article the main emphasis is put on real options which may be understood as the options to modify different projects. The real options analysis reflects the value of strategic options that are often embedded in corporate real investments. The limitations of geometric Brownian motion, if applied to commodity prices, are shown mainly because price changes are not independent of one another. So the paper indicates that there is a need to incorporate mean reversion processes while modelling commodity prices, especially energy and copper prices. As an example the simplest and most commonly used mean reverting process - Ornstein-Uhlenbeck process - is analyzed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 193-203